FRI0485 18f-fluorodeoxyglucose positron emission tomography in elderly patients with an elevated erythrocyte sedimentation rate of unknown origin. (23rd January 2014) - Lensen, K. D. F.; Voskuyl, A. E.; van der Laken, C. J.; Comans, E. F. I.; van Schaardenburg, D.; Arntzenius, A. B.; Zwijnenburg, T.; Stam, F.; Gompelman, M.; van der Zant, F.; van Paassen, A. Q.; Voerman, B.; et al.
Abstract : Background: Patients with an elevated erythrocyte sedimentation rate (ESR) and non-specific symptoms often pose a diagnostic dilemma. PET/CT visualises infection, inflammation and malignancy, all of which may cause elevated ESR. Objectives: To determine the contribution of 18F-fluorodeoxglucose positron emission tomography (PET/CT) in the diagnostic work-up of referred patients with an elevated ESR, in whom initial routine evaluation did not reveal a diagnosis, in order to detect large vessel vasculitis, among other diseases. Methods: In a combined retrospective (A) and prospective (B) study PET/CT was performed in elderly patients (> 50 years of age) who presented with a significantly elevated ESR (≥ 50 mm/h) and non-specific complaints. In addition, a protocolised work-up (including chest X-ray, abdominal ultrasound and protein electrophoresis) was used in study B. In both studies, the final diagnosis was based on histology, clinical follow-up, response to therapy and/or additional imaging. Results: In study A, 30 patients were included. PET/CT results suggested malignancy (8 patients), inflammatory disease (8 patients, including 5 with large-vessel vasculitis) and infection (3 patients). In 2 patients, non-specific abnormalities were found. Of the 21 patients with abnormal PET/CT results, final diagnoses were in accordance with PET/CT results in 12 patients (including 5 with large-vessel vasculitis). In 9 patients, abnormalities detected by PET/CT did not contribute to the final diagnosis. Two diagnoses (tendinitis and acute myeloid leukaemia) were established in 9 patients with a normal scan. In study B, 58 patients were included. PET/CT results suggested inflammatory disease (25 patients), particularly large-vessel vasculitis (14 cases), infection (5 patients) and malignancy (3 patients). 7 scans demonstrated non-specific abnormalities. Of the 40 patients with abnormal PET/CT results, final diagnoses were in accordance with PET/CT results in 22 patients (including 14 with large-vessel vasculitis). In 18 patients PET/CT abnormalities did not contribute to a final diagnosis. One final diagnosis (PMR) was established in 20 patients with a normal scan. Conclusions: PET/CT may be of potential value in the diagnostic work-up of patients with non-specific complaints and an elevated ESR. In particular, large-vessel vasculitis appears to be a common finding. A normal PET/CT scan in these patients suggests that it is safe to follow a wait-and-see policy. Disclosure of Interest: None Declared